Analisis Efektivitas Pemeriksaan Pajak Wajib Pajak Badan Dalam Meningkatkan Penerimaan Pajak Penghasilan Badan Pada Kantor Pelayanan Pajak Wajib Pajak Besar Empat Tahun 2019 - Sunarti Sunarti; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2021)
This research is conducted to analyze the Effectiveness of Corporate Taxpayer Tax Audit in Increasing Corporate Income Tax Revenue at the Large Taxpayer Tax Office Four in 2019 and to analyze the inhibiting and driving Entities in the effectiveness of the implementation of the audit of corporate taxpayers in increasing corporate income tax revenue at the Large Taxpayer Tax Office Four. Data collection techniques were carried out by interviewing, observing, studying literature /documentation and sources triangulation. The results of the study concluded that the effectiveness of the Tax Audit in the Large Taxpayer Tax Office Four in 2019 has not reached optimal results because of the targets set have not yet been achieved. This is partly due to the lack of Audit Orders Letter (SP2) number of special audits and difficulties in collecting data both internal and external. It is recommended that the Large Taxpayer Tax Office Four increase the number of SP2 special audits by supervising strategic taxpayers through comprehensive research activities, focusing on allocating available resources to conduct more precise and effective supervision and auditing of Taxpayers. Data limitations should not be an obstacle in tax audits. Therefore, the Large Taxpayer Tax Office Four must provide easy access to internal and external data retrieval to produce an optimal audit. In addition, the Large Taxpayer Tax Office Four in order to provide counseling/outreach to taxpayers to increase taxpayer knowledge of tax regulations, which is expected to be able to increase the level of awareness of taxpayers who are still low about the tax audit conducted.